Pengaruh Teknologi Informasi Akuntansi dan Sistem Pengukuran Kinerja terhadap Kinerja Manajerial pada Satuan Kerja Perangkat Daerah Kota Bukittinggi - Fadhilatul Husna; Fefri Indra Arza (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to determine the effect of accounting information technology and performance measurement systems on managerial performance (an empirical study on the Regional Work Unit of the City of Bukittinggi). The population in this study were all 28 regional work units of the City of Bukittinggi. The sample collection technique used is total sampling. The researcher took 3 samples for each SKPD, namely the head of the SKPD, the secretary and the financial advisor. So that the number of samples is 84. This type of research is quantitative research. The data source in this study is primary data, which is the research data source obtained directly from the original source. In this study obtained from answers to questionnaires distributed to respondents who became the sample in this study. Data analysis using multiple linear regression analysis. The results of this study indicate that accounting information technology and performance measurement systems have a positive and significant effect on managerial performance.